PENGEMBANGAN EVALUASI PEMBELAJARAN BERBASIS MULIMEDIA DENGAN FLASH, PHP, DAN MYSQL - Sutopo, Hadi (Jurnal Informatika, 2009)
Computer-Based Testing (CBT) program was launched for years to give testtakers the options of taking computerized version of test. The application which genarate academic score is developed as a server-side with Adobe Flash. Flash is well known as a powerful and dynamic front-end for the Web. However, Flash is also great interface for server-side applications. PHP can launch server-side script using Flash as a front-end and pass variables back and forth between Flash and the PHP pages. Along with PHP, MySQL can be used to store data and later retrieve it. Using Flash as a front-end, data and variables are passed between the MySQL database, PHP, and Flash to enchance aplication's functionality in managing databases.